IL-12 Expands and Differentiates Human Vγ2Vδ2 T Effector Cells Producing Antimicrobial Cytokines and Inhibiting Intracellular Mycobacterial Growth - Yang, Rui; Yao, Lan; Shen, Ling; Sha, Wei; Modlin, Robert L.; Shen, Hongbo; Chen, Zheng W. (Frontiers in Immunology, 2019)
While IL-12 plays a key role in differentiation of protective CD4+ Th1 response, little is known about mechanisms whereby IL-12 differentiates other T-cell populations. Published studies suggest that predominant Vγ2Vδ2 T cells in humans/nonhuman primates (NHP) are a fast-acting T-cell subset, with capacities to rapidly expand and produce Th1 and cytotoxic cytokines in response to phosphoantigen (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP) produced by Mycobacterium tuberculosis (Mtb) or others. However, whether IL-12 signaling pathway mediates fast-acting and Th1 or anti-microbial features of Vγ2Vδ2 T cells remains poorly defined. Here, we show that IL-12, but not other IL-12 family members IL-27/IL-35, apparently expanded HMBPP-activated Vγ2Vδ2 T cells. Although IL-12 and IL-2 similarly expanded HMBPP-activated Vγ2Vδ2 T-cell clones, the IL-12-induced expansion did not require endogenous IL-2 or IL-2 co-signaling during HMBPP + IL-12 co-treatment. IL-12-induced expansion of Vγ2Vδ2 T cells required the PI3K/AKT and STAT4 activation pathways and endogenous TNF-α signaling but did not involve p38/MAPK or IFN-γ signals. IL-12-expanded Vγ2Vδ2 T cells exhibited central/effector memory phenotypes and differentiated into polyfunctional effector cell subtypes which expressed TBX21/T-bet, antimicrobial cytokines IFN-γ, TNF-α, GM-CSF, and cytotoxic granule molecules. Furthermore, the IL-12-expanded Vγ2Vδ2 T cells inhibited the growth of intracellular mycobacteria in IFN-γ- or TNF-α-dependent fashion. Our findings support the concept that IL-12 drives early development of fast-acting Vγ2Vδ2 T effector cells in antimicrobial immune responses.